Aspek Hukum Penolakan Klaim Oleh Perusahaan Asuransi dalam Kasus Fraud Klaim Asuransi - Dana Ihlassul Alanjung (Jurnal sosial dan sains, 2026)
This study examines the legal issues that arise when insurance companies refuse to pay claims on the grounds of alleged fraud or fraud from the insured. Claim rejection is the right of the insurance company based on the provisions of the policy and laws and regulations, but its implementation must meet the appropriate procedures and not violate the rights of the insured. The main problem in this study is how to protect the legal for insured who face claim rejection due to indications of fraud, as well as the legal impact for insurance companies who refuse incorrectly. The research method used is normative juridical with a legislative and case approach, analyzing various regulations such as the Commercial Law, Law Number 40 of 2014 concerning Insurance, and related Financial Services Authority Regulations. The results of the study show that the insured has legal protection through the complaint mechanism to the Financial Services Authority, mediation, arbitration, and litigation in court. Insurance companies that illegally reject claims can be subject to administrative sanctions, the obligation to pay compensation, and even the revocation of business licenses. This research contributes to understanding the balance between the right of insurance companies to reject claims that contain fraud and the obligation to provide protection to insured in good faith.